Structure and Challenges of Nigeria’s Overseas Diplomatic Missions - Aremu, Johnson Olaosebikan (European Scientific Journal, ESJ, 2016)
This paper is committed to an historical exploration of the structure, functions and challenges of Nigeria’s overseas missions since inception till 1999. To this end, it employed the eclectic method of enquiry, adopting a combination of historical and descriptive methods of data collection. The study relies heavily on secondary data sourced from journal articles, textbooks, newspapers and magazines and other relevant materials including government gazettes. It also benefitted significantly from primary sources of information. Facts and information obtained were subjected to corroboration and critical analysis using qualitative method. This was done in order to enhance objectivity. The paper observes that Nigeria’s overseas missions fall into two broad categories, namely, the diplomatic and consular missions and are of varying sizes. These missions have vigorously pursued the country’s national interest over the years with mixed results of success and failures, amidst daunting challenges.